The Need to Look for Visual Deficit After Stroke in Children - Luckman, Judith; Chokron, Sylvie; Michowiz, Shalom; Belenky, Eugenia; Toledano, Helen; Zahavi, Alon; Goldenberg-Cohen, Nitza (Frontiers in neurology, 2020)
Purpose: To evaluate the role of the ophthalmologist in the management of children with arterial stroke, at presentation and during follow-up. Methods: This retrospective case series comprised children with arterial stroke who were followed for at least 12 months in a tertiary pediatric medical center in 2005-2016. Demographic data and findings on radiological neuroimaging and ophthalmological and neurological examination were retrieved from the medical files. Results: The cohort included 26 children with stroke. Underlying disorders included metabolic syndrome (n = 5, 19.2%), cardiac anomaly or Fontan repair (n = 3 each, 11.5%), vascular anomaly (n = 3, 11.5%), head trauma with traumatic dissection (n = 3, 11.5%), and hypercoagulability (n = 1, 3.8%); in eight patients (30.8%), no apparent cause was found. Eleven patients (42.3%) had a non-ophthalmological neurological deficit as a result of the stroke. Eye examination was performed in nine patients (34.6%) during follow-up. Ophthalmological manifestations included hemianopic visual field defect in seven patients (7.7%) and complete blindness and poor visual acuity in one patient each (3.8%). At the last visit, no change in visual function was detected. Conclusion: The variable etiology and presentation of pediatric stroke may mask specific visual signs. Children with arterial stroke should be referred for early ophthalmological evaluation and visual rehabilitation.Purpose: To evaluate the role of the ophthalmologist in the management of children with arterial stroke, at presentation and during follow-up. Methods: This retrospective case series comprised children with arterial stroke who were followed for at least 12 months in a tertiary pediatric medical center in 2005-2016. Demographic data and findings on radiological neuroimaging and ophthalmological and neurological examination were retrieved from the medical files. Results: The cohort included 26 children with stroke. Underlying disorders included metabolic syndrome (n = 5, 19.2%), cardiac anomaly or Fontan repair (n = 3 each, 11.5%), vascular anomaly (n = 3, 11.5%), head trauma with traumatic dissection (n = 3, 11.5%), and hypercoagulability (n = 1, 3.8%); in eight patients (30.8%), no apparent cause was found. Eleven patients (42.3%) had a non-ophthalmological neurological deficit as a result of the stroke. Eye examination was performed in nine patients (34.6%) during follow-up. Ophthalmological manifestations included hemianopic visual field defect in seven patients (7.7%) and complete blindness and poor visual acuity in one patient each (3.8%). At the last visit, no change in visual function was detected. Conclusion: The variable etiology and presentation of pediatric stroke may mask specific visual signs. Children with arterial stroke should be referred for early ophthalmological evaluation and visual rehabilitation.